Uso de aplicativos tecnológicos no ensino de teatro - Teixeira, Fabíola Morais Agripino (2018)
The present work seeks to bespeak and analyze the possible ways to use the Communication and Information Technologies (ICTs) in the mediation between the performative utterances, built along with the students of the Municipal School of Arts - Casa das Artes - and its feedback with the performer students. A set of theatrical and improvisational games were used aiming to construct an active learning presence. The experience was performed practically, and developed into two performative utterances. The first one, having as stimulus the urban space within a conception of Corpocidade / Corpografia; and the second, the poetry of Paraiba as a field of experimentation, both aimed at developing performative experiments from the game in the relationships between body, voice, space and time, building a present body action being later shared in the virtual environment. The research brings an analysis of the possible reflections made from a smartphone screen and from the look of the students / performers, taking the virtual space as an expanded territory of learning and sharing of knowledge.